2021
DOI: 10.1002/advs.202001100
|View full text |Cite|
|
Sign up to set email alerts
|

A Micropatterned Human‐Specific Neuroepithelial Tissue for Modeling Gene and Drug‐Induced Neurodevelopmental Defects

Abstract: The generation of structurally standardized human pluripotent stem cell (hPSC)‐derived neural embryonic tissues has the potential to model genetic and environmental mediators of early neurodevelopmental defects. Current neural patterning systems have so far focused on directing cell fate specification spatio‐temporally but not morphogenetic processes. Here, the formation of a structurally reproducible and highly‐organized neuroepithelium (NE) tissue is directed from hPSCs, which recapitulates morphogenetic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…The development of neuruloids suggest that early ectodermal morphogenesis is an autonomous process, as non-ectodermal lineages are absent in this system. This contrasts with recent work suggesting that endoderm-derived TGFβ signalling supports the folding of the neural tube in a micropattern model comprising both mesendodermal and neurectodermal tissues ( Sahni et al, 2021 ). I should note that these two observations are not incompatible.…”
Section: Micropattern Models Of Early Mammalian Embryogenesiscontrasting
confidence: 99%
“…The development of neuruloids suggest that early ectodermal morphogenesis is an autonomous process, as non-ectodermal lineages are absent in this system. This contrasts with recent work suggesting that endoderm-derived TGFβ signalling supports the folding of the neural tube in a micropattern model comprising both mesendodermal and neurectodermal tissues ( Sahni et al, 2021 ). I should note that these two observations are not incompatible.…”
Section: Micropattern Models Of Early Mammalian Embryogenesiscontrasting
confidence: 99%
“…Bioengineered in vitro models have become powerful tools to study relationships between biophysical microenvironments and intracellular signaling pathways that align to specify cell fate in populations of pluripotent stem cells. [ 47 , 48 ] In recent years, micropatterned systems have shown how geometric confinement can guide cellular assembly, where triggering differentiation with soluble morphogens has led to in vitro models of embryogenesis, [ 12 , 13 , 49 ] neuroectoderm, [ 50 , 51 ] vascular, [ 17 , 52 ] and cardiac tissue. [ 22 ] While these models relied on soluble factors to initiate differentiation, here we demonstrated how pluripotent stem cells micropatterned on deformable substrates initiated in vitro morphogenesis‐like events through interactions with the substrate alone.…”
Section: Discussionmentioning
confidence: 99%
“…We induced human ESCs into midbrain and hindbrain cells in the presence of low dosages of VPA and isotretinoin. Penicillin G was used as a non-teratogenic control since it has been shown that it does not disrupt neural tube development at its peak plasma concentration [44][45][46] . First, we performed cell proliferation assay to measure cell viability under treatment with different concentrations of these three tested drugs (Supplementary Figure 10).…”
Section: Drug-induced Developmental Defects In Early Midbrain and Hin...mentioning
confidence: 99%